Auditor Type as Moderating of the Determinants of Intellectual Capital Disclosure - Kurniawan, Ichsan; Baroroh, Niswah (Universitas Negeri Semarang, 2021)
This research intends to examine the effect of an independent board of commissioners, firm size, and leverage on intellectual capital disclosure and to test the auditor type as moderator. The measurement of intellectual capital disclosure uses content analysis. The research population is consumer good industry manufacturing companies listed on the Indonesia Stock Exchange 2016-2018. The research sample was taken using the purposive sampling technique with 105 units of analysis. The research data collection method uses the documentation method. The data were analyzed using descriptive statistical analysis techniques and inferential analysis. Hypothesis testing uses moderated regression analysis. The results showed that firm size has a positive effect and leverage has a negative effect on intellectual capital disclosure. Auditor type moderates the effect of leverage on intellectual capital disclosure. The independent board of commissioners does not affect intellectual capital disclosure. Auditor type does not moderate the effect of the independent board of commissioners and firm size on intellectual capital disclosure. The conclusion of this study shows that the disclosure of intellectual capital will be higher in large firms and auditor type will increase the disclosure of intellectual capital in firms with high leverage. Keywords: Intellectual capital disclosure; Independent board of commissioners; Firm size; Leverage; Auditor type